Effects of High Temperature Aging Treatment on the Microstructure and Impact Toughness of Z2CND18-12N Austenitic Stainless Steel - Hui Zhang; Yanfeng Liu; Xian Zhai; Wenkai Xiao (Metals, 2020)
During the casting cooling process or the forging process, austenitic stainless steel will remain at around 800 °C for some time. During this period, precipitate particle behaviors in austenitic stainless steel (containing ferrite) will cause a reduction in ductility, which can lead to material cracking. In this study, the effects of aging at 800 °C on the microstructure, impact toughness and microhardness of Z2CND18-12N austenitic stainless steel were systematically investigated. The precipitation processes of the χ and σ phases were characterized by color metallography and back scattered electron (BSE) signals. The toughness was investigated by the Charpy impact test. After the aging treatment, the χ and σ phases precipitated successively in the ferrite, and as the aging duration increased, the χ-phase dissolved and the σ-phase precipitated along the austenite grain boundaries. These all lead to a decrease in toughness and an increase in microhardness. Finally, the relationship between fracture morphology and aging time is discussed herein, and a crack mechanism is given.